Peran Orang Tua Terhadap Sikap Seksual Remaja - Ni Luh Putu Veronica E.D.S.; Fitriani Mediastuti; Andina Vita Sutanto (Jurnal Ilmu Kebidanan (Journal of Midwivery Science), 2013)
Background: one of factors which influence adolescent sexual attitudes is role of parents. Teens get very little information about the sexuality education from their parents. Bantul has 135 cases of early marriage (LPA, 2012). The survey data of early marriage incidence in Terong Village indicate 21 cases in 2012.Objective: To determine the relationship of parents to adolescent sexual attitudes in Pencitrejo Hamlet, Terong Village, Dlingo Sub-district.Methods: The study quantitative method with cross sectional design. Sampling used purposive sampling with as many as 60 respondents of teens and 60 respondents of parents of teens. Types of primary data with research instrument using questionnaire. Data analysis used chi square.Results: There were 18 respondents of parents have high role for adolescent and teenagers who has parents with high role has positive sexual attitudes. Positive sexual attitudes is adolescent who do not have the attitudes deviation in sexual behavior. Parents who has quite role for adolescent, there were34 respondent, and teenagers with positive sexual attitudes as many as 32 respondents of teens (94,1%) and negative sexual attitudes as many as 2 respondents of teens ((5,9%). Whereas parents who has less role for adolescent, there were 8 respondents, with teenagers who has positive sexual attitudes as many as 1 respondent (12,5%) and negative sexual attitudes as many as 7 respondents (87,5%). Chi square analysis with p value= 0,000.Conclusion: there is a relationship between role of parents to adolescent sexual attitudes in Pencitrejo Hamlet, Terong Village, Dlingo Sub-district and statistically significant (p=0,000).Keywords: role, parents, sexual attitudes, adolescents